Integrated analysis of paraquat-induced microRNAs-mRNAs changes in human neural progenitor cells. (October 2017) - Yan, Mengling; Dou, Tingting; Lv, Wen; Wang, Xinjin; Zhao, Lina; Chang, Xiuli; Zhou, Zhijun
Abstract: Paraquat (PQ), one of the most widely used fast-acting and non-selective herbicides in the world is believed to act as a neurotoxicant, which increases the risk of developing Parkinson's disease (PD) by selectively impairing dopaminergic neurons. However, the mechanism of PQ on neural progenitor cells remains unclear. As regulator of mRNA expression, miRNA play a crucial role in neurotoxicity. Based on our previous study, we chose 10 μM PQ, which induced ROS production and inhibited proliferation but not reduced the cell viability. In this study, we present an integrative analysis of PQ-induced whole transcriptome changes and its regulatory miRNA networks in human neural progenitor cells (hNPCs). Integrated analysis of PQ-induced miRNA-mRNA alteration reveals differential expression of 3972 mRNAs and 52 miRNAs. Based on the GO analysis and pathway analysis of the intersection genes, we found 48 significantly altered GO terms and 22 significant pathways, among which, Wnt signaling being the top-ranked pathway. We verified that the expression of 9 miRNAs and 11 mRNAs related to the Wnt signaling pathway were altered in a dose-dependent manner by qPCR. These results indicate that PQ changes mRNAs and miRNAs expression in hNPCs, leading to the alteration of several neurodevelopment related key biological processes and crucial pathways, especially Wnt signaling pathway. Moreover, it suggests that PQ could downregulate Wnt signaling pathway via miRNA to induce developmental neurotoxicity. Highlights: PQ alters mRNAs and miRNAs expression in human neural progenitor cells (hNPCs). PQ causes the change of several neurodevelopment related key biological processes. PQ leads to the alteration of several neurodevelopment related crucial pathways. PQ could downregulate Wnt signaling pathway via miRNA in hNPCs.